Singapore [videorecording] - The Travel Preview System (Houston, Tex. Travelview International, 1996)
Describes Singapore as the Garden City of Southeast Asia.
Title on container: Singapore : the beginning of a great vacation.
VHS.
Keywords: Singapore -- Description and travel